A randomized controlled pilot study of the University of Minnesota mentoring excellence training academy: A hybrid learning approach to research mentor training. Issue 4 (18th August 2019) - Weber-Main, Anne Marie; Shanedling, Janet; Kaizer, Alexander M.; Connett, John; Lamere, Michelle; El-Fakahany, Esam E.
Abstract: Introduction: Research mentor training is a valuable professional development activity. Options for training customization (by delivery mode, dosage, content) are needed to address the many critical attributes of effective mentoring relationships and to support mentors in different institutional settings. Methods: We conducted a pilot randomized controlled trial to evaluate a hybrid mentor training approach consisting of an innovative, 90-minute, self-paced, online module ( Optimizing the Practice of Mentoring, OPM ) followed by workshops based on the Entering Mentoring (EM) curriculum. Mentors ( n = 59) were randomized to intervention or control arms; the control condition was receipt of a two-page mentoring tip sheet. Surveys (pre, post, 3-month follow up) and focus groups assessed training impact (self-appraised knowledge, skills, behavior change) and participants' perceptions of the blended training model. Results: The intervention (∼6.5 hours) produced significant improvements in all outcomes, including skills gains on par with those reported previously for the 8-hour EM model. Knowledge gains and intention-to-change mentoring practices were realized after completion of OPM and augmented by the in-person sessions. Mentors valued the synergy of the blended learning format, noting the unique strengths of each modality and specific benefits to completing a foundational online module before in-person engagement. Conclusions: Findings from this pilot trial support the value of e-learning approaches, both as standalone curricula or as a component of hybrid implementation models, for the professional development of research mentors.